An experimental and numerical analysis of concrete walls exposed to fire - Baghdadi, Mohamed; Dimia, Mohamed S; Guenfoud, Mohamed; Bouchair, Abdelhamid (Structural Engineering and Mechanics, An Int'l Journal, 2021)
To evaluate the performance of concrete load bearing walls in a structure under horizontal loads after being exposed to real fire, two steps were followed. In the first step, an experimental study was performed on the thermo-mechanical properties of concrete after heating to temperatures of 200-1000oC with the purpose of determining the residual mechanical properties after cooling. The temperature was increased in line with natural fire curve in an electric furnace. The peak temperature was maintained for a period of 1.5 hour and then allowed to cool gradually in air at room temperature. All specimens were made from calcareous aggregate to be used for determining the residual properties: compressive strength, static and dynamic elasticity modulus by means of UPV test, including the mass loss. The concrete residual compressive strength and elastic modulus values were compared with those calculated from Eurocode and other analytical models from other studies, and were found to be satisfactory. In the second step, experimental analysis results were then implemented into structural numerical analysis to predict the post-fire load-bearing capacity response of the walls under vertical and horizontal loads. The parameters considered in this analysis were the effective height, the thickness of the wall, various support conditions and the residual strength of concrete. The results indicate that fire damage does not significantly affect the lateral capacity and stiffness of reinforced walls for temperature fires up to 400oC.